Women in AI: is there a Singapore model? - Nair, Tamara (2022)
The 4ᵗʰ Industrial Revolution introduced Machine Learning and Artificial Intelligence (AI) to the forefront and very soon, if not already, AI will be embedded in almost all spheres of our lives. While AI technologies like Alexa and Siri have female names and voices, there are very few women involved in developing AI products and services. Is there a model Singapore can offer?